Long-Term Impact Of Major Road Investments On The Transformation Of The Regional And Country Settlement Structure - A Case Study Of Lower Silesia - Katarzyna Iwaszko (European Regional Science Association (ERSA), 2012)
The paper analyze the impacts of infrastructure investments on clusters of directions and development trends of contacts made through the road network. The present settlement system is a particular system of interconnected elements. These connections are part of a network of accessibility which influences the development of concentration and hierarchy of the structure. The creation or termination of new connections leads to completely different spatial characteristics of entire networks, and thus influences the possibility to create contacts and develop particular areas. Up to the 20th century the communication system was determined by the geographical space. The popularization of new means of transport and the development of infrastructure, i.e. bridges, highways, overpasses and tunnels improved the speed of traveling and reduced the dependence on geographical conditions. The accessibility of communication became equivalent to the duration of a trip rather than its distance. By introducing new, significantly faster connections or by overcoming topographical barriers, we gradually change the whole settlement structure. The paper presents results of investigation on transportation network, curried out characterization of the transport network as a factor which delimits development of areas. The studies implement an original cyclical-complex model based on T. Zipser's theory of contacts and theory of spherical projection. The method refers to the ways of standardization of descriptions of states and phenomena of various research aspects concerning the same space which is particularly essential in network issues, where the anisotropy of an infrastructure is deal with. In contrast to illustrations, which do not contain any more data than the tables upon which they are based, this analysis is in itself a research tool. Owing to visual integration and theoretical interpretation it enables us to read the morphology of the whole structure, which is otherwise not evident. The study focuses on the region of Lower Silesia divided into communes (gminas). The study includes analyses of the communication network in the early 20th century, the network system of 1937 with the opened Berlin-Wrocław highway, and the current communication network with consideration of the Polish National Highway Development Plan.
Keywords: 330; communication networks; communication accessibility; communication efficacy; settlement structures